Gambaran Pola Asuh Dan Status Gizi Balita Pada Keluarga Perokok Di Kecamtan Berastagi Tahun 2014 - Dwinta Julian Sasmi; Etti Sudaryati; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Parenting parents has significant impact on the life of children in the future. One of the growth inhibitory effect of parenting which is not oriented to the development of childern. It usually occurs in under five years old. The objective of the study was to describe the parenting and nutritional status of five under years old in smokers families in Berastagi District in 2014. This research was a descriptive cross-sectional design. Data was collected by inter views and questionnaires to 100 respondents with five  under year old in the region of sub-district healath centers Berastagi in March-June 2014. The results showed that the majority of mother who have five under year old in smoker families were with good parenting category, which consisted of 64% feeding practices, hygiene practices and environmental sanitation 64%, and the care of children and families in sickness 67%. The results of measurements of weight/height according to the WHO 2005 standards were in the category off at 1%, 3% risk of fat, 73% normal, 17% lean, and very skinny 6%. The results of measurements of nutritional knowledge a were in either category that was equal to71%, and the knowledge of smoking were in the good category at 68%. Counseling  is required on food, nutrition and health to mothers who have  five under years old in smoker families so that knowledge, parenting and a good level of consumption can be further improved and will ultimately improve the nutritional status of children. Key words : parenting, nutritional status,  five under years old, smoker families